GABAergic Interneurons Control Adult Neurogenesis but Astrocytes Have the Last Word - Trinchero, Mariela Fernanda (2020)
Adult neurogenesis depends on the decision of neural stem cells to leave quiescence and become neurons. In this issue, Asrican et al. show that the neuropeptide cholecystokinin released by interneurons promotes the neuronal fate through astrocytic signaling.